SIMULATION OF THE NEURAL NETWORK TO SOLVE TASKS OF SYMBOLS IDENTIFICATION - Vasyura, Anatolyy; Martynyuk, Tetyana; Kupershtein, Leonid (Scientific Works of Vinnytsia National Technical University, 2011)
Modeling of the three layer feed forward neural network is executed for symbols identification in context of using this network in the neural part of the fraud management system in telecommunications. Modeling is executed by using MatLAB 6.5 and toolkit Neural Networks Toolbox.